Familial inheritance of the 3q29 microdeletion syndrome: case report and review - Wahab A. Khan; Ninette Cohen; Stuart A. Scott; Elaine M. Pereira (BMC, 2019)
Abstract Background The chromosome 3q29 microdeletion syndrome is characterized by a clinical phenotype that includes behavioral features consistent with autism and attention deficit hyperactivity disorder, mild to moderate developmental delay, language-based learning disabilities, and/or dysmorphic features. In addition, recent data suggest that adults with chromosome 3q29 microdeletions have a significantly increased risk for psychosis and neuropsychiatric phenotypes. Case presentation We report a 3-year-old male with global developmental delay, anemia, and mild dysmorphic facial features. Clinical chromosomal microarray (CMA) testing of the proband detected a heterozygous 1.21 Mb deletion at chromosome 3q29, consistent with a diagnosis of the 3q29 microdeletion syndrome. Interestingly, subsequent parental testing determined that the pathogenic deletion was inherited from his otherwise healthy mother who had a history of learning disabilities. The chromosome 3q29 microdeletion was not detected in the healthy older sibling of the proband by CMA testing, nor was it prenatally detected in a subsequent maternal pregnancy. Conclusion Our report highlights the 3q29 microdeletion syndrome as an illustrative example of the importance of a molecular diagnosis for families that harbor pathogenic copy number aberrations with variable expressivity, in particular those that also impart an increased risk for adult onset neuropsychiatric phenotypes.